IMPLEMENTATION OF NETWORK WEBSITE TECHNOLOGY IN COMPANY BRANDING PROFILE - Wisnu Sukma Maulana; Andre Pratama Adiwijaya (Asosiasi Dosen Muda Indonesia, 2023)
A website is a network-based information medium that can be accessed anywhere and anytime using a computer. It is relatively inexpensive compared to conventional information media such as newspapers. We can do many things by using a website, one of which is to inform about a company, also known as a company profile. The research method used is WDLC. In the testing phase, three different web browsers were used. When tested on these three browsers, there were no bugs at all.